ANALISIS KEMAMPUAN BERPIKIR “RAKUS” DALAM MENGHADAPI TANTANGAN PENDIDIKAN ABAD 21 - Moh. Taufiq Farisman Abdulah; Krisbiantoro; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of the society 5.0 era requires the education system to be able to prepare students with high-level thinking skills. This study aims to describe and analyze the application of RAKUS (Rational, Analytical, Critical, Universal, and Systematic) thinking patterns in the learning process in class 5A of SD Muhammadiyah Ponorogo. This study used a descriptive qualitative approach to explore in depth the process and form of implementation of RAKUS thinking skills through observation, interviews, and documentation. Data were analyzed aspirationally and interpretatively according to the Miles and Huberman paradigm. The results showed that the majority of students had been able to actualize the RAKUS aspect significantly, with a percentage reaching 80-87%, although there were some students who were not optimal. Problem-solving-based learning, group discussions, and reflection are effective strategies for developing RAKUS thinking skills. The application of RAKUS thinking patterns in elementary schools is a strategic step in preparing a smart, critical, and adaptive young generation to face complex and dynamic future challenges.